The Flat Type Heat Pipe Solar Collector: An Experimental Research - Dian Wahyu (Jurnal Teknik Mesin (JTM), 2016)
Flat solar collectors with heat pipe absorber with dimension of wide 1.5 m x 2 m lenght x 0.2 m thickness and 2.87 m2 aperture area has been tested to produce hot water. Heat pipe used in flat plate solar collector, has a filling ratio of 20% which has been proven to have the highest ability to transfer heat when tested in previous studies. Testing of solar collectors with heat pipe absorber has been done during the month of April 2016 in the city of Padang by using standard ASHRAE 93-2003. The test results showed the highest efficiency obtained was 46%. To get the hot water of at least 64 ° C with a flow rate of 0,35 L / min for 5 hours, required solar radiation of 750 W / m2. Generally, during the trial obtained water output temperature collectors from 8:00 - 9:00 pm and from 15: 30 - 17: 30 is below 60 ° C, whereas at 9:30 - 15: 30 obtained collector output water temperature above 64 ° C, while the water temperature reached at the highest collector output value of 78 ° C.